Oproportionerligt intresse? En undersökning av proportionalitetsprincipen i plan- och byggärenden. - Backman,Alexander (2025)
This essay analyses the balance between private and public interest in matters relating to the Planning and building act of 2010 according to which there has to be a fair balance of interests. This essay also analyses how the previous relates to the European convention and the Instrument of Government and if there is a need for a stronger protection of private interests. According to the Planning and building act, municipalities have the monopoly on planning and building in their geographical area. Sometimes they even have a duty of creat-ing detailed zoning plans. Because of this property owners sometimes need a permit to be allowed to build on their property. In matters relating to this, both public and private interests need to be reviewed so that the burden carried by the private part isn’t too heavy. This also needs to meet the demands that fol-lows by the same review according to the European convention and the In-strument of Government. Even if a decision has legal basis in the Planning and building act it also must have basis in the European convention and the instrument of Government. Through case law, Swedish law and legal litera-ture it has been shown that there is no big conflict between the three principles of proportionality. It has also been found in case law the most important as-pect is for how many years the municipality has denied building permits with the motivation of the duty of creating detailed zoning plans. In other cases, denial of applications, have been overruled by Swedish courts when the mu-nicipality failed to show reasons for why the public interest was the most im-portant. Finally, with regards to the case law, I believe that there is reason to strengthen private interests in these issues. I also believe that there is reason for a stronger protection in Swedish law for the protection of private property.
Keywords: Fastighetsrätt; Statsrätt; Plan- och bygglagen; Regeringsformen; Europakonventionen; Proportionalitetsprincipen; Detaljplaner